2017
DOI: 10.18632/oncotarget.15227
|View full text |Cite
|
Sign up to set email alerts
|

Geraniin attenuates LPS-induced acute lung injury via inhibiting NF-κB and activating Nrf2 signaling pathways

Abstract: Geraniin, a typical ellagitannin isolated from Phyllanthusurinaria Linn, has been reported to have anti-inflammatory effect. The aim of the study is to investigate the therapeutic effects of geraniin on LPS-induced acute lung injury (ALI) in mice. The mice were intranasal adminisration of LPS for 12 h. Geraniin was intra-peritoneal injection 1 h after LPS treatment. The results showed that geraniin significantly attenuated LPS-induced pathological changes in the lung. Geraniin also inhibited LPS-induced macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 33 publications
2
24
1
Order By: Relevance
“…Our data show a significant increase in the expression of Nrf2 in lung homogenate of mice treated with adenine suggesting that adenine treatment could trigger adaptive responses that counterbalance the potentially damaging activity of oxygen radicals induced by adenine administration. Our data corroborate the finding of a recent study which showed that Nrf2 expression is increased in lipopolysaccharide (LPS)-induced lung injury in mice (Zhu et al, 2017 ). In the same study, it was shown that geraniin, an ellagitannin isolated from Phyllanthusurinaria Linnnatural which has anti-inflammatory and antioxidant actions, inhibited NF-κB activation and induced an up-regulation of Nrf2 expression that resulted in the attenuated LPS-induced acute lung injury (Zhu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…Our data show a significant increase in the expression of Nrf2 in lung homogenate of mice treated with adenine suggesting that adenine treatment could trigger adaptive responses that counterbalance the potentially damaging activity of oxygen radicals induced by adenine administration. Our data corroborate the finding of a recent study which showed that Nrf2 expression is increased in lipopolysaccharide (LPS)-induced lung injury in mice (Zhu et al, 2017 ). In the same study, it was shown that geraniin, an ellagitannin isolated from Phyllanthusurinaria Linnnatural which has anti-inflammatory and antioxidant actions, inhibited NF-κB activation and induced an up-regulation of Nrf2 expression that resulted in the attenuated LPS-induced acute lung injury (Zhu et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…2A) with febuxostat treatment, we searched for other potential sources of ROS. As LPS leads to an influx of inflammatory cells, that is, neutrophils (Zhu et al 2017), we measured myeloperoxidase activity as marker of neutrophil-generated ROS. As shown in Figure 2 Xanthine Oxidoreductase, there is marked increase in myeloperoxidase activity after LPS exposure.…”
Section: Inhibiting Xor With Febuxostat Does Not Improve Lipopolysaccmentioning
confidence: 99%
“…Geraniin, the main polyphenolic compound of geraniums [11,13], was first isolated from Geranium thunbergii [14]. The beneficial effects of geraniin, including antiinflammatory and anti-cancer effects in LPS-induced macrophages by inhibiting NF-κB and Nrf2 signaling pathways, as well as its antioxidant activities, have been reported [14][15][16]. However, the ameliorating effects of geraniin on esophageal damages in RE via anti-inflammatory activities have not been reported.…”
Section: Introductionmentioning
confidence: 99%